Elaboración de un código de integridad para la gerencia de proyectos de inversión pública en Colombia (2019)
The purpose of this document is to contribute to the strengthening of ethics and professional conduct in the management of public investment projects in Colombia, through the creation of an integrity code that guides the actions of the people involved in a public investment project. . The research carried out is of a qualitative and descriptive approach, derived from the literature review, interviews, surveys and expert judgment. The results of the literary review are combined, which allows to identify the state of the art of ethics at national and international level; from the interviews, which refers to the structure of the integrity code; and from the surveys, which have information on the content of the integrity code. Finally, the proposal is validated by experts from the perspective of axiology, project management and the public sector. According to the consolidated information, it is concluded that people linked to public investment projects receive attention in the fulfillment of ethics and transparency in the development of their daily functions; however, the commitment in its daily task oriented to the common good is evident. In addition, we identified the idea of ​​this proposal was well received because there is an expectation of an instrument that guides and mitigates the ethical problems that arise for public servants and contractors.